2015
DOI: 10.1109/tnb.2015.2501364
|View full text |Cite
|
Sign up to set email alerts
|

A Graphene and Aptamer Based Liquid Gated FET-Like Electrochemical Biosensor to Detect Adenosine Triphosphate

Abstract: Here we report successful demonstration of a FET-like electrochemical nano-biosensor to accurately detect ultralow concentrations of adenosine triphosphate. As a 2D material, graphene is a promising candidate due to its large surface area, biocompatibility, and demonstrated surface binding chemistries and has been employed as the conducting channel. A short 20-base DNA aptamer is used as the sensing element to ensure that the interaction between the analyte and the aptamer occurs within the Debye length of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 34 publications
0
29
0
1
Order By: Relevance
“…Aptamers are extensively used to study small molecule metabolites (Paige et al , 2012; Feng et al , 2014) and are analyzed by variety of methods such as fluorescence spectroscopy (Sun et al , 2010; Park et al , 2015b; Wang et al , 2015; Song et al , 2016) electrochemistry (Mukherjee et al , 2015; Zhao et al , 2015), surface plasmon resonance (Park et al , 2015a) and colorimetry (Huo et al , 2016). Aptamers can be engineered to detect ATP in nanomolar to millimolar ranges; however, cell permeability and degradation issues limit their use in live-cell imaging (Wang et al , 2014).…”
Section: Methods For Detection and Imaging Atpmentioning
confidence: 99%
“…Aptamers are extensively used to study small molecule metabolites (Paige et al , 2012; Feng et al , 2014) and are analyzed by variety of methods such as fluorescence spectroscopy (Sun et al , 2010; Park et al , 2015b; Wang et al , 2015; Song et al , 2016) electrochemistry (Mukherjee et al , 2015; Zhao et al , 2015), surface plasmon resonance (Park et al , 2015a) and colorimetry (Huo et al , 2016). Aptamers can be engineered to detect ATP in nanomolar to millimolar ranges; however, cell permeability and degradation issues limit their use in live-cell imaging (Wang et al , 2014).…”
Section: Methods For Detection and Imaging Atpmentioning
confidence: 99%
“…I). [74][75][76][77]80] At the end of this review, we will discuss in details that recent progresses on operating GFETs at high frequencies suggested that Debye screening can be overcome: [46] 1.…”
Section: Debye Screeningmentioning
confidence: 99%
“…Possible routes to circumvent the Debye screening effect include short antibody design, porous polymer incorporation, and ex situ measurement in low ionic strength buffers (see Section 2.5). [74][75][76][77]80] These approaches, however, also impose limitations on the biodetection and it is highly desirable to develop a straightforward methods to overcome the Debye screening: [46] 1. without any special design or engineering of the receptor molecules and the sensor environments, and 2. in physiological conditions to facilitate in-situ, real-time biosensing. Theoretically, improved sensitivity is expected at high frequencies using a measuring strategy that overcomes the ionic screening effect.…”
Section: Overcoming the Debye Length Limitations With Radio-frequencymentioning
confidence: 99%
“…So in fact, the Debye screening effect has put a fundamental obstacle to the possible sensing applications of the GFETs (and ISFETs in general) for real‐time detection of relatively large biomolecules at high‐salt/physiological conditions, although in principle GFETs are sensitive to changes below one single charge . Indeed, various approaches have been pursued to circumvent the Debye screening effect toward ultimate detection of biomolecules, including rational design of short antibodies, ex situ measurement in low ionic strength buffers, and incorporation of porous polymer layers permeable to biomolecules . Nevertheless, to achieve highly sensitive, real‐time detection in high‐salt/physiological conditions without any specific aptamer molecular design and restriction on interface environment, more general and novel operation strategy still have to be developed.…”
Section: Principle Fabrication and Operation Of Graphene Nanoelectrmentioning
confidence: 99%